Linfoma cutâneo em equino Quarto de Milha - dos Santos, Fernanda Carlini; Ugolini, Lays Wouters; Oliveira, Henrique Ramos; Machado, Tanise Policarpo; Alves, Leonardo Porto (Acta Scientiae Veterinariae, 2017)
Background: Lymphoma, although rare, is the most common hematopoietic neoplasia in horses. The overall incidence of lymphoma is between 1.3-2.8% of all equine neoplasia and it has a prevalence of 0.002-0.5% in the equine population. Lymphoma can be classified as multicentric, alimentary, mediastinal, cutaneous and solitary. The cutaneous is the rarest form and it usually presents with multifocal skin lesions, with no other clinical signs. The diagnoses is accomplished by histopathological examination of a biopsy or cytological examination of a fine needle aspirate. The aim of the current study is to report a case of the rarest form of equine lymphoma, the cutaneous. Case: An 8-year-old equine female, Quarter Mile, was evaluated due to volume’s increase and subcutaneous nodules disseminated along the body. These lesions developed gradually during 2 years. The mare was used for ridding, it was kept in the field with 10 other equines and was the only one affected. The mare was vaccinated for influenza and was negative for glanders and equine infectious anemia. During clinical exam, all vital parameters were within limits and body condition score was classified as 6 (Henneke Chart). It was observed bilateral nasal secretion and depigmentation in ocular and vulvar mucous. It was observed multiple delimited areas with size ranging from few cm up to 7 cm, hard, mobile, painless, located in the subcutaneous and disseminated in the body (including head, neck, thorax, limbs and perineum). Red blood cell, leucocytes, fibrinogen, total plasmatic protein were within normal limits. Due to clinical signs and the potential risk of a zoonosis, the glanders test was repeated (complement fixation test) and the result was negative. Differential diagnoses also included insect hypersensitive, which was discarded since the female did not presented pruritus nor alopecia, lesions gradually increased in size and no seasonality was observed. It was performed excisional biopsy for tissue culture, which revealed no growth of aerobic mesophile bacteria. Histopathological evaluation revealed rounded cell proliferation similar to lymphocytes situated in the deep derma and subcutaneous. After evaluation of history, clinical exam and complementary exams the mare was diagnosed with cutaneous lymphoma. The owner was instructed that there was no available specific treatment with good efficacy and viable for equines at this stage. Besides, it is important to evaluated the mare constantly due the possibility of future lesions in organs or intern lymph nodes. Discussion: Cutaneous lymphoma is an uncommon disease, especially in horses, that can present with variable clinical signs, immunosuppression, rapid systemic disease progression or none at all. In the present case report, during clinical examination lesions were observed in areas of lymphatic drainage. Identification of neoplastic lymphocytes during cytological examination or histopathological evaluation of biopsy tissue can confirm the presence of lymphoma, as performed in the present case. Treatment is palliative and occasionally results in complete cure, mainly in equine with single lesions. The mare had cutaneous lymphoma disseminated all long the body and no clinical signs that could suggest gastrointestinal neoplastic lesions, even though the owner was advised that this animal should be monitored regularly in the future, specially due the possibility of metastatic lesions in any other organ. In equine, lymphoma has low incidence and the cutaneous form is the rarest one. Clinical signs are typically non specific and develop insidiously, so it is important to perform complementary exams for accurate diagnoses and for differential diagnoses of tegumental and infectious diseases.